Analisis Miskonsepsi Pelayanan Bimbingan dan Konseling di SMA dan MAN Idi Rayeuk - Khairirani Khairirani; Muhammad Nasir; Rizky Andana Pohan (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2021)
A misconception is a wrong explanation and an idea that is incompatible with the scientific understanding accepted by the experts. Misconceptions often occur because the concepts learned and accepted by students are different. The purpose of this study was to determine how the misconception of guidance and counseling services in SMA and MAN Idi Rayeuk. This research was conducted using qualitative descriptive methods with data collection techniques through observation, interviews, and documentation. The results of this study explain that the misconception of guidance and counseling services in MAN 1 Idi Rayeuk still occurs because the teacher who serves as a counseling teacher is not a BK teacher but is a graduate of Sociology who is given the responsibility to solve student problems, less because they do not understand the theory and how to implement the BK services provided to students to deal with their problems. Meanwhile, in SMA N 1 Idi Rayeuk, misconceptions do not occur, because the teachers who provide BK services are graduates of S-1 guidance and counseling. The service and implementation of the BK program have started to be carried out well because BK teachers are able to carry out their duties in implementing BK services in accordance with the operational guidelines for the implementation of guidance and counseling for high school (SMA).